IDENTIFICAÇÃO DA ORIGEM DE MANIFESTAÇÕES PATOLÓGICAS DETECTADAS EM ASSISTÊNCIA TÉCNICA - Brandstetter, Maria Carolina; Chagas, Letícia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The anomalies and building pathologies that appears post-occupancy affect the building company brand, generate inconveniences to the users and costs not foreseen in the building planning. The objective of this study was to analyze the data registered in the technical assistance of a building, evaluating the possible origin of building pathologies as to: design, construction, material or use failures. A case study was conducted in a residential building with the data collection obtained from the construction company based on records of technical assistance requests. As to the origin of the anomalies and defects, the results obtained were that approximately 46% of the anomalies are caused by construction failures, followed by 27% related to material failures, 21% due to use failures and 6% related to the design failures. The analysis of the building technical assistance requests is an important management tool capable of pointing out the stages in the life cycle of the building that originated the most anomalies emphasizing the moments that require more controls and interventions.